From Spasms to Strength: Rehabilitating West Syndrome - Pooja Thakur (Disease and Health: Research Developments Vol. 9, 2025)
This abstract explores Infantile spasms (aka West syndrome), which is a severe form of epilepsy that typically occurs in infancy and can cause developmental delays in early life, cognitive impairment, and motor dysfunction. While pharmacological treatments such as adrenocorticotropic hormone (ACTH) therapy and antiepileptic drugs are essential for managing seizures, physiotherapy plays a crucial role in improving motor outcomes and enhancing the overall development of infants. Early intervention focuses on reducing spasms by improving muscle strength, bilateral coordination, and the development of gross motor skills such as rolling, sitting, and crawling, which are often delayed in children with West syndrome. Tailored therapeutic exercises and movement strategies can minimize the impact of developmental regression and help children reach age-appropriate motor milestones. Hence the aim of this chapter is to create awareness for the parents and therapists so that early diagnosis can be done and multidisciplinary treatment can be started. Working closely with other healthcare providers to ensure comprehensive care, supporting the child’s physical and neurological development. Early and consistent physiotherapy can significantly improve functional abilities and quality of life for children with West syndrome.